2014
DOI: 10.1007/s10508-014-0264-8
|View full text |Cite
|
Sign up to set email alerts
|

A Man with Urethral Polyembolokoilamania Successfully Treated with Electroconvulsive Therapy

Abstract: Polyembolokoilamania is the act of inserting foreign objects into bodily orifices and can be classified as a paraphilia if done for sexual pleasure. Although problematic sexual behaviors are common in dementia, the majority of case reports of urethral polyembolokoilamania in the elderly have occurred in the absence of dementia or cognitive impairment. Little empirical evidence exists for managing problematic sexual behaviors in the elderly and in dementia. Most evidence in the form of case reports demonstrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A case report mentioned one such case where OCD and depression were co-morbid in a case of frontotemporal dementia who exhibited urethral polyembolokoilamania. [ 15 ] All three of our cases were diagnosed from this spectrum and followed up with the treatment of OCRD.…”
Section: Discussionmentioning
confidence: 99%
“…A case report mentioned one such case where OCD and depression were co-morbid in a case of frontotemporal dementia who exhibited urethral polyembolokoilamania. [ 15 ] All three of our cases were diagnosed from this spectrum and followed up with the treatment of OCRD.…”
Section: Discussionmentioning
confidence: 99%
“…Polyembolokoilamania, a term reported as inser on of foreign objects into natural body orifices mostly by pediatric pa ents, adults with compromised mental status and at mes deliberate inser on via body orifice done for other mo ves like ero c pleasures and malingering are not new to 2,3 literature. However, in the presented case, sewing needles were not inserted through the orifices, but penetrated through the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Firoz et al [33] reported a case of fetishism with comorbid substance abuse that was successfully treated with naltrexone. Ingves et al [34] reported the successful treatment of a 67-year-old man suffering from depression, obsessive-compulsive disorder, and signs of frontotemporal dementia with a course of electroconvulsive therapy. Because of the coincidence of Parkinson's disease and compulsive sexual behaviour, the potential case of an individual with Parkinson's disease and paedophilia is an example for an ethical treatment dilemma.…”
Section: Therapeutic Approachmentioning
confidence: 99%